Design of an Internal Quality Assurance System Based on Smart System to Improve the Quality of Higher Education at Universitas Garut - Ramdani, Dendi; Winda Suwandi, Deden; Fauzan Wakila, Yasya; Sabilul Muminin, Riyad (RISTEC : Research in Information Systems and Technology, 2023)
Garut University has a Quality Assurance Institute (LPM) responsible for overseeing the quality assurance cycle, but it still uses manual archiving, leading to data accumulation and slow performance. This research aims to develop an internal quality assurance system based on a smart system to improve the quality of higher education. The research method uses a waterfall approach with stages of data collection, system analysis, application design, and implementation. The system is designed to effectively distribute and store LPM data and information. The research results show that this information system can help improve the quality of higher education by providing quick and accurate information related to data standards and audits.